The Effect of Health Education About Scabies on The Behavior of Students at The Al-Ulfah Rancah Boarding School - Heni Marliany; Hana Istikomah; Asep Gunawan (LPPM STIKes Muhammadiyah Ciamis, 2023)
Scabies does not endanger human life, but it is very disturbing to feel comfortable and can reduce activity and productivity, this skin disease is often found in highly populated environments such as in Islamic boarding schools. Health education is needed to provide information about scabies to students, because the lack of knowledge and behavior can be one of the factors causing scabies. This study was to determine the effect of health education about scabies on the behavior of students in Al-Ulfah Rancah boarding school. This research design is Pre-Experimental one group pretest-posttest design. The number of samples in this study were 43 respondents. Sampling using purposive sampling technique. Data were collected by questionnaire. It is known that before being given health education about scabies to 43 respondents, there were 14 respondents (32.55%) who fell into the bad category and 29 respondents (67.45%). This study shows that after being given health education about scabies, 2 respondents (4.65%) were in the bad category and 41 respondents (95.35%) were in the good category with an average increase of 11.79. It can be concluded that there is a significant influence between health education about scabies on the behavior of students. Thus it is expected to make a sustainable program, especially regarding the behavior of preventing scabies by paying attention to the environment and personal hygiene.